Norwegian Bay Quadrangle, Minnesota - St. Louis County, 1964: 7.5 Minute Series (Topographic) Map - United States Department of the Interior Geological Survey; State of Minnesota, Department of Conservation (Iron Range Research Center, 1964)
Norwegian Bay quadrangle topographic map (N4752.5-W9230/7.5) featuring handwritten notations by Ray Segar in pencil and red ink regarding logging railroad lines in the Kabetogama State Forest area.